Hadith #286 - Sahih Muslim - Sa`d from his father (Sahih Muslim)
The Messenger of Allah (ﷺ) ignored some of them. And he who was ignored seemed to be more deserving in my eyes (as compared with others). I (Sa’d) said: Messenger of Allah I why is it that you did not give to such and such (man)? Verily I see him a believer. Upon this the Messenger of Allah (ﷺ) observed: Or a Muslim? I kept quiet for some time but I was again impelled (to express) what I knew about him. I said: Messenger of Allah why is it that you did not give it to such and such? Verily,
Grade: Sahih

Hadith #287 - Sahih Muslim - Sa`d from his father (Sahih Muslim)
The Messenger of Allah (ﷺ) bestowed upon a group of persons (booty) and I was sitting with them. The remaining part of the hadith is the same as mentioned (above) with the additionI stood up and went to the Messenger of Allah (ﷺ) and whispered to him: Why did you omit such and such a man?
Grade: Sahih

Hadith #2317 - Sahih Muslim - Sa`d from his father (Sahih Muslim)
Messenger of Allah, what about so and so? By Allah, I find him a believer. He (the Messenger of Allah) said: He may be a Muslim. I kept quiet for a short while, and then what I knew of him urged me (to plead his case again) and I said: Messenger of Allah, what about so and so? By Allah, I find him a believer. Upon this he (the Holy Prophet) said: He may be a Muslim. I again remained quiet for a short while, and what I knew of him again urged me (to plead his case so I) said: Messenger of Allah,
Grade: Sahih

Hadith #5743 - Sahih Muslim - Sa`d from his father (Sahih Muslim)
It is better for the belly of any one of you to be stuffed with pus rather than to stuff (one’s mind) with poetry.
Grade: Sahih

Hadith #6063 - Sahih Muslim - Sa`d from his father (Sahih Muslim)
Aren’t you satisfied with being unto me what Aaron was unto Moses?
Grade: Sahih

Hadith #6082 - Sahih Muslim - Sa`d from his father (Sahih Muslim)
This verse was revealed in relation to six persons and I and Ibn Mas’ud were amongst them. The polytheists said to him (the Holy Prophet): Do not keep such persons near you. It was upon this that (this verse was revealed):” Drive not away those who call upon their Lord morning and evening desiring only His pleasure” (vi. 52).
Grade: Sahih

Hadith #6083 - Sahih Muslim - Sa`d from his father (Sahih Muslim)
We were six men in the company of Allah’s Messenger (, nay peace be upon him) that the polytheists said to Allah’s Apostle (ﷺ): Drive them away so that they may not be overbold upon us. He said: I, Ibn Mas’ud and a person from the tribe of Hudhail, Bilal and two other persons, whose names I do not know (were amongst such persons). And there occurred to Allah’s Messenger (ﷺ) what. Allah wished and he talked with himself that Allah, the Exalted and Glorious, revealed:” Do not drive a
Grade: Sahih